Characterization of the Modular Design of the Autolysin/Adhesin Aaa from Staphylococcus Aureus - Hirschhausen, Nina; Schlesier, Tim; Peters, Georg; Heilmann, Christine (PLOS ONE, 2012)
Background Staphylococcus aureus is a frequent cause of serious and life-threatening infections, such as endocarditis, osteomyelitis, pneumonia, and sepsis. Its adherence to various host structures is crucial for the establishment of diseases. Adherence may be mediated by a variety of adhesins, among them the autolysin/adhesins Atl and Aaa. Aaa is composed of three N-terminal repeated sequences homologous to a lysin motif (LysM) that can confer cell wall attachment and a C-terminally located cysteine, histidine-dependent amidohydrolase/peptidase (CHAP) domain having bacteriolytic activity in many proteins. Methodology/Principal Findings Here, we show by surface plasmon resonance that the LysM domain binds to fibrinogen, fibronectin, and vitronectin respresenting a novel adhesive function for this domain. Moreover, we demonstrated that the CHAP domain not only mediates the bacteriolytic activity, but also adherence to fibrinogen, fibronectin, and vitronectin, thus demonstrating for the first time an adhesive function for this domain. Adherence of an S. aureus aaa mutant and the complemented aaa mutant is slightly decreased and increased, respectively, to vitronectin, but not to fibrinogen and fibronectin, which might at least in part result from an increased expression of atl in the aaa mutant. Furthermore, an S. aureus atl mutant that showed enhanced adherence to fibrinogen, fibronectin, and endothelial cells also demonstrated increased aaa expression and production of Aaa. Thus, the redundant functions of Aaa and Atl might at least in part be interchangeable. Lastly, RT-PCR and zymographic analysis revealed that aaa is negatively regulated by the global virulence gene regulators agr and SarA. Conclusions/Significance We identified novel functions for two widely distributed protein domains, LysM and CHAP, i.e. the adherence to the extracellular matrix proteins fibrinogen, fibronectin, and vitronectin. The adhesive properties of Aaa might promote S. aureus colonization of host extracellular matrix and tissue, suggesting a role for Aaa in the pathogenesis of S. aureus infections.